La responsabilidad social de Comfenalco y empresa de Energía del Quindío: características y realidades (2013)
Starting from the observation of the documents published by companies, the evaluation of academic positions and the studying of the standards, this document intend to characterize the CSR reports issued by two companies localized in the department of Quindío. The manuscript is done by identifying how these enterprises performance into planning, executing and accounting for their actions in favor to society in general. The analysis includes the exploration of the similarities of these documents with the definitions proposed by different academic currents and the levels of influence and implementation of the national and international laws standards. Through this text we identify the weaknesses and strengths of each report in order to establish an assessment of the correspondence between academic actors, regulators and the directives view into the way they recognize the impacts of business in society. From the light into the previous context, it appears that companies are determined, in a big proportion to report on their social programs, instead than realize their actions in society.